SUPPORTING PIONEERS: BUILDING BETTER NETWORKS FOR ADULTS AGING WITH AUTISM. (11th November 2018) - Waldron, D A; Coyle, C E; Kramer, J; Jeckel, D
Abstract: Although traditionally understood as a childhood condition, autism spectrum disorder (ASD) is a lifelong disorder present in both children and adults. However, many of the children with this disorder who were born during the last century and who are now reaching mid and later life did not receive formal diagnoses of ASD—leaving them facing the second half of life with new portions of their identity. For adults with ASD, getting older means an accumulation of limited social networks and the aging of their own family system, housing instability, and financial insecurity. This presentation presents results from 25 in-depth, in-person, life course interviews with adults aging with ASD. Results highlight the importance of transitions of social support for these adults as they seek to meet their needs in later life and features of community living that create more inclusivity of adults living with ASD, including opportunities for social engagement.